Science Centres and Science Events A Science Communication Handbook - Bruyas, Anne-Marie.; Riccio, Michaela; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2013)
The idea for this text stemmed from the fruitful experience gathered during the training course of 9 Nigerian university students organized in Naples from 3 to 18 September 2008 by the team of Fondazione IDIS-Città della Scienza under the project Science Centre Owerri. The training course turned out to be not only an educational opportunity to acquire knowledge and skills for these students, but also a real and practical tool that later led to the realization of the first Science Festival of Owerri in Nigeria in May 2009. This in turn sparked the idea of creating a highly practical handbook for those who want to face the challenge of developing new projects for the dissemination and socialization of science in developing countries. In these countries, the role of scientific education and training in schools is not sufficient to arouse scientific curiosity among young people and make the population aware of the importance of scientific knowledge in everyday life. Moreover science and technology are indispensable tools for people s empowerment and should be supported with actions that encourage curiosity about science and the intelligent use of technology to bridge the divide with developed countries. It is therefore necessary to set up activities that are carefully targeted to promote and communicate science. The text has been designed as a practical guide to be used in a variety of contexts: scientific events or more structured science festivals, training, the creation of scientific cultural associations, and the development of new science centres. Besides being an excellent tool for training and supporting the design and planning phases, the manual can also be used as a reference work for institutions and local cultural services which have to select projects of this type.
Foreword by L. Brito -- Introduction by A.-M. Bruyas and M. Riccio -- Part I Science in Society -- Toward Knowledge Societies by G.V. Silvestrini -- Science and Society by P. Greco -- Science Communication at Glance by L. Amodio -- Part II -- The Evolution and World-Wide Expansion of Science Centres by V. Lipardi -- Part III Practical Guidelines to approach science communication -- The cooperation project for a new Science Centre in Owerri, Nigeria by A.-M. Bruyas -- Lesson 1. Activities and Tools Overview by G. Maglio -- Lesson 2. The Role of Exhibition in Museum and Science Centre by A. Porro and L. Cerri -- Lesson 3. Design Process for the Organization of Exhibition Areas by M.T. Pica Ciamarra -- Lesson 4. Educational Activities by M. Campanino -- Lesson 5. Conferences and Debates by R. Parente and A. Zanazzi -- Lesson 6. Science Festival by D. Angela Palma -- Lesson 7. Communication and Media Plan by C. Guardascione -- Lesson 8. Training Explainers by F. Iuliano -- Lesson 9. Visitor Needs by F. De Matteis -- Lesson 10. Communication Techniques with Visitors by D. Petrone -- Lesson 11. Participatory Tools: the EASW Methodology by L. Simeone -- Lesson 12. Visit to Square wheels exhibition Calitri by P. Cerreta -- Lesson 13. Science Theatre by E. De Capoa -- Lesson 14. Appetizer to the Italian language and culture by F. Sibilio and R. Giordano -- From Theory to Practice by G. Maglio -- Part IV -- Cookbook of Science Demos selected by G. Maglio -- Workshop 1. Chemistry by G. Gaeta and E. Rampone -- Workshop 2. Food Education by F. Di Martino -- Workshop 3. Energy by A. Porro and R. Parente -- Workshop 4. Environment by G. Maglio -- Workshop 5. Music and science by M. Campanino -- Other examples of activities and projects -- Science for Peace in the Middle East Project by A.-M. Bruyas -- ACCENT - Action on Climate Change for Engagement, Network and Tools by F. Di Martino -- TIME for Nano-Tools to Increase Mass Engagement for Nanotechnology by A. Drioli.
Keywords: Social sciences; Science education; Management; Social Sciences; Cultural Management; Science Education; Social Sciences, general; Electronic books